2014
DOI: 10.1039/c3ee42934b
|View full text |Cite
|
Sign up to set email alerts
|

3D ordered macroporous LaFeO3 as efficient electrocatalyst for Li–O2 batteries with enhanced rate capability and cyclic performance

Abstract: Xin-Bo Zhang et al. 3D ordered macroporous LaFeO 3 as effi cient electrocatalyst for Li-O 2 batteries with enhanced rate capability and cyclic performance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
236
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(251 citation statements)
references
References 49 publications
9
236
0
1
Order By: Relevance
“…One of the primary reasons hierarchical CBPM are used as electrodes is their high surface area, with a higher active area for a given volume of material. High surface area allows for easy access to active materials in batteries 75,421,423,426,[428][429][430][431] and fuel cells, 432,433 improving energy density. It also leads to higher dye loading, and thus increased light absorption and higher rates, in dye-sensitized solar cells.…”
Section: Factors Influencing Electrode Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the primary reasons hierarchical CBPM are used as electrodes is their high surface area, with a higher active area for a given volume of material. High surface area allows for easy access to active materials in batteries 75,421,423,426,[428][429][430][431] and fuel cells, 432,433 improving energy density. It also leads to higher dye loading, and thus increased light absorption and higher rates, in dye-sensitized solar cells.…”
Section: Factors Influencing Electrode Applicationsmentioning
confidence: 99%
“…341,458 Much like for catalysis, the macroporous structure of CBPM provides for easier diffusion to the active surface; in electrodes, fast ion diffusion means faster charging and reaction rates. 430 Ordered, inverse structures have been particularly well investigated as a means of controlling ion transport, for example in Li-ion batteries, 26,428,466 Li-air batteries, 431 dye-sensitized solar cells (DSSC), 450 and fuel cells. 432,433 These colloid-templated structures have also been used as separators in batteries 184 and fuel cells 434 due to their ability to control ion diffusion.…”
Section: Factors Influencing Electrode Applicationsmentioning
confidence: 99%
“…In the search for more affordable catalytic materials, a number of researchers have devoted their effort to developing metal oxide catalysts with high activity and to utilising them in MABs. [116][117][118][119][120][121][122][123][124][125][126] In particular, spinel-type transition metal oxides have attracted great attention as catalytic materials for MABs due to their relatively low cost and high activity. Spinel-type transition metal oxides based on Co, Mn and/or Ni have been reported to exhibit strong bi-functionality towards the ORR and OER in aqueous alkaline electrolytes: 11,89,127 ORR-OER:…”
Section: View Article Onlinementioning
confidence: 99%
“…So far, great efforts have been devoted to developing the cathode catalyst with high activity and stability for oxygen-involved reactions in Li-O2 batteries [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Peng et al [7] firstly reported the rechargeable Li-O2 batteries by catalyzing the reversible formation/decomposition of the Li2O2 on porous Au catalyst, which makes Li-O2 batteries promising for practical use.…”
Section: Introductionmentioning
confidence: 99%